Infrastructure Health Monitoring System (SHM) Development, a Necessity for Maintenance and Investigation - Priyo Suprobo; . Faimun; Arie Febry (University of Bandar Lampung (UBL), 2013)
Failure of Kutai Bridge already gives Indonesia civil engineer a blow in face. The failure which bring cause human accident make a new challenge to Indonesia civil engineer not to wait till failure but to safe before the construction failure. By the development in sensor and monitoring technology the idea become more realistic. Structure Healthy Monitoring (SHM) become new idea to detect, to monitor and to find out the reliability of structure. The development and research in Indonesia for SHM till now are presented and compared to other country. SHM research is needed to predict behavior of bridge by using data from monitoring to gain healthy condition.